2002
DOI: 10.1007/s00431-002-0957-1
|View full text |Cite
|
Sign up to set email alerts
|

Long-term follow-up of children with bacterial meningitis with emphasis on behavioural characteristics

Abstract: Except for hearing impairment, severe sequelae after bacterial meningitis which are not discovered at discharge do not appear later. Children who appear well after bacterial meningitis have more non-specific symptoms like headache, and more signs and symptoms indicating inattention, hyperactivity and impulsiveness than their siblings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
2
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 32 publications
2
23
2
1
Order By: Relevance
“…9 In the majority of reviews, the follow-up period was not defined. 7,9,17 By defining "long-term" as a follow-up period of 5 or more years, our review showed that the majority of survivors with sequelae that are documented in the literature described academic and behavioral limitations. Minor neurologic deficits have been shown often to resolve after discharge.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…9 In the majority of reviews, the follow-up period was not defined. 7,9,17 By defining "long-term" as a follow-up period of 5 or more years, our review showed that the majority of survivors with sequelae that are documented in the literature described academic and behavioral limitations. Minor neurologic deficits have been shown often to resolve after discharge.…”
Section: Discussionmentioning
confidence: 96%
“…This observation differs from other comprehensive literature reviews, which define "long-term" as occurring any time following the time of hospital discharge, which describe a much higher prevalence of neurologic and hearing deficits. 7,9,17,18 For example, the literature review by Ramakrishnan et al (2009) looking at sequelae from bacterial meningitis among African children found that a median of 25% of children had 1 or more neuropsychological sequelae. 9 In the majority of reviews, the follow-up period was not defined.…”
Section: Discussionmentioning
confidence: 97%
“…The reported worldwide frequency of neurological sequelae has varied from 10-50% ,21 but from the developed world it is around 10-20%. [4][5][6][7][8][9] Various studies • *Total children with neurological sequelae not mentioned in the study, but various sequelae noted were spasticity-6, hemiparesis-5, quadriparesis-1, and ataxia-1. • # Mean age in Pneumoccocal meningitis group: 12.5 months and in Haemophilus influenzae-b group: 9.8 months.…”
Section: Discussionmentioning
confidence: 96%
“…Various clinical and laboratory parameters have been implicated in the prognosis of acute bacterial meningitis. Almost all the published information regarding long term neurodevelopmental outcome has come from developed countries [5][6][7][8][9][10][11][12] with a few reports of systematic research regarding this from developing countries [13][14][15][16] including India. 17,18 The authors have studied the long-term neurological and developmental outcome following an episode of acute bacterial meningitis, and clinical and laboratory predictors of the long-term neurological outcome.…”
mentioning
confidence: 98%
“…Long-term sequelae due to these processes of neuronal death include deafness, intellectual and cognitive impairment ranging from severe intellectual disability to educational deficits and behavioural problems, and less commonly epilepsy, spasticity, or focal neurologic deficits. (9,12,15,24,44,140).…”
Section: The Neuronmentioning
confidence: 99%